Udder health inflammatory markers in camel milk (Camelus dromedarius) and milk yield - Tinggren, Sofie (2019)
Kenya is one of the biggest producers of camel milk in the world. Apart from milk production, camels are also a very important source of food and income for pastoralists. Camels (Camelus dromedarius) are well adapted to the harsh environments and arid parts of the country. Mastitis is one of the most common and costly diseases of dairy animals because of loss in milk yield and cost of treatment. The quality of the milk also decreases due to mastitis and the milk will be worth less. Mastitis can affect the storage life of the milk, which can lead to a loss in income. The aim of this literature review was to obtain a greater understanding of why camel milk has become so popular and what challenges the milk industry in Kenya must overcome. The aim of the field study was to investigate if there were any associations between the inflammatory markers, somatic cell count (SCC), N-acetyl-BD-glucosaminidase (NAGase) and lactate dehydrogenase (LDH), udder skin temperature or the California mastitis test (CMT), and subclinical mastitis or decreased quarter milk yields in affected quarters in camels. Descriptive statistic of the distribution of the inflammatory markers and milk yield were performed as well as statistical analyses of associations between each inflammatory marker and milk yield. The inflammatory markers SCC, NAGase, LDH and CMT appeared to be good markers for subclinical mastitis in Camelus dromedarius. The udder skin temperature did not work well as a marker for subclinical mastitis in this study. Milk yield did not show any relationship with CMT or with SCC. The percentage difference in milk yield between paired udder quarters nevertheless indicated that a high CMT was associated with a decreased milk yield up to 44.7%. However, more research is needed. As CMT is an easy and cheap way of detecting udder quarters with subclinical mastitis, it could be used as a measurement to improve udder health and camel milk quality in pastoral camel herds in Kenya.